Immobilized Native Bacteria as a Tool for Bioremediation of Soils and Waters: Implementation and Modeling - C. Lobo; M. Sanchez; C. Garbi; E. Ferrer; M.J. Martinez-Iñigo; J.L. Allende; C. Martinez; L. Casasas; R. Alonso; A. Gibello; M. Martin (The Scientific World Journal)
Based on 3,4-dihydroxyphenylacetate (3,4-DHPA) dioxygenase amino acid sequence and DNA sequence data for homologous genes, two different oligonucleotides were designed. These were assayed to detect 3,4-DHPA related aromatic compound—degrading bacteria in soil samples by using the FISH method. Also, amplification by PCR using a set of ERIC primers was assayed for the detection of Pseudomonas GCH1 strain, which used in the soil bioremediation process. A model was developed to understand and predict the behavior of bacteria and pollutants in a bioremediation system, taking into account fluid dynamics, molecular/cellular scale processes, and biofilm formation.